Policy Brief: The Role Of Health Education Regarding Cervical Cancer Screening In Universities - Paripurna, Yoga (JURNAL KEBIDANAN, 2024)
Cervical cancer is one of the leading causes of death among women worldwide, including in Indonesia. Although it can be prevented through cervical cancer screening such as Pap smears and HPV tests, many women, including students, are unaware of the importance of routine screening. Universities, as educational institutions with a significant female student population in a vulnerable age group, play a crucial role in raising awareness and encouraging participation in cervical cancer screenings. However, several challenges exist, including low awareness among students about cervical cancer, social stigma, limited access to medical services, and the lack of integration of health education into the Curriculum.This policy brief aims to provide policy recommendations that universities can implement to address these issues. Key recommendations include integrating health education on cervical cancer into the Curriculum, collaborating with health institutions to provide screening services on campus, and developing sensitive and inclusive awareness campaigns. By increasing knowledge, reducing stigma, and improving access to services, this policy is expected to enhance student participation in cervical cancer screening, reduce mortality rates from cervical cancer, and foster a healthier reproductive health culture among students.These policies promise positive impacts on student health and have the potential to enhance the University's reputation as an institution that cares about its students' well-being. Successful implementation of this policy will reduce the prevalence of cervical cancer among young women and improve the overall quality of life for students.